2012
DOI: 10.1038/ncomms1810
|View full text |Cite
|
Sign up to set email alerts
|

TEMPRANILLO genes link photoperiod and gibberellin pathways to control flowering in Arabidopsis

Abstract: In Arabidopsis, FLOWERING LOCUS T (FT) promotes flowering in response to long days in the photoperiod pathway, while signalling downstream gibberellin (GA) perception is critical for flowering under short days. Previously we have established that the TEMPRANILLO (TEM) genes have a pivotal role in the direct repression of FT. Here we show that TEM genes directly regulate the expression of the GA 4 biosynthetic genes GA 3-oxidase1 and 2 (GA3OX1 and GA3OX2). Plants overexpressing TEM genes resemble GA-deficient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
188
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(212 citation statements)
references
References 33 publications
(47 reference statements)
14
188
1
1
Order By: Relevance
“…In concordance with our findings, the expression of GA20ox1 is slightly downregulated in the Arabidopsis soc1 mutant (DorcaFornell et al, 2011), but the effect of this change on growth is unknown. SOC1 may also regulate the GA biosynthetic pathway by repressing TEMPRANILLO1 (Tao et al, 2012), which downregulates GA3ox1 and GA3ox2 by binding to their promoters (Osnato et al, 2012). Although our results strongly suggest that Fv SOC1 controls the GA biosynthetic pathway in strawberry, genetic experiments combining silencing of GA biosynthetic genes with Fv SOC1 overexpression or vice versa would be necessary to confirm our findings.…”
Section: Fv Soc1 Regulates Vegetative Development By Activating Ga Bisupporting
confidence: 61%
“…In concordance with our findings, the expression of GA20ox1 is slightly downregulated in the Arabidopsis soc1 mutant (DorcaFornell et al, 2011), but the effect of this change on growth is unknown. SOC1 may also regulate the GA biosynthetic pathway by repressing TEMPRANILLO1 (Tao et al, 2012), which downregulates GA3ox1 and GA3ox2 by binding to their promoters (Osnato et al, 2012). Although our results strongly suggest that Fv SOC1 controls the GA biosynthetic pathway in strawberry, genetic experiments combining silencing of GA biosynthetic genes with Fv SOC1 overexpression or vice versa would be necessary to confirm our findings.…”
Section: Fv Soc1 Regulates Vegetative Development By Activating Ga Bisupporting
confidence: 61%
“…This relay of information from GA to SOC1 occurs through degradation of the DELLA proteins RGA and RGL2 with a partial contribution from RGL1 (Cheng et al, 2004). In addition, GA has been shown to regulate flowering by interacting with photoperiod, ambient temperature and vernalization pathways (Galvão et al, 2015;Jung et al, 2012;Li et al, 2015;Osnato et al, 2012). The effect of GA is also spatially regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the flowering activators CO, FT, LEAFY (LFY), and APETALA1 (AP1) are induced, but the flowering repressor FLC (FLOWERING LOCUS C) is repressed in low-nitrate conditions (12,13). There are also reports that nitrate availability controls the GA pathway at different levels (GA biosynthesis, perception, and signaling) to influence the timing of vegetative to reproductive phase change (13,14). However, Castro Marín et al (15) showed that low nitrate induced flowering by a pathway downstream of the floral integrators and independent of photoperiod, GA, and autonomous pathways.…”
mentioning
confidence: 99%